Porang Flour as an Alternative Substitute for Wheat Flour in Food Production - Sriwulandari, Tatik; Saleha, Saleha; Suparmono, Bambang; Ramadhan, Hesqy (Prasetiya Mulya Publishing, 2023)
Porang can be used as an alternative substitute for wheat flour in food production because it contains insoluble and insoluble fiber and has low levels of glucose and fat to anticipate the potential cardiovascular disease. This study aims to determine the effect of differences in the substitution of wheat flour with porang flour on the level of panelists acceptance. Experimental research method with the design of 2 variations of substitution of wheat flour and porang flour respectively 0:100% and 20:80%. The results showed that 100% porang flour substitution was preferable to 80% porang flour substitution. Significant and real differences were proven by using Kruskal-Wallis test and Mann Whitney test on the criteria for color, aroma, texture and taste, with a p-value less than 0.05 and an average value above 3.00. It was concluded that panelists preferred Ketapang Seed cookie using 100% porang flour as a substitute for wheat flour.